(untitled) (Baghdad Science Journal, 2025)
Toxoplasmosis is an infection caused by Toxoplasma gondii that leads to abortion or hydrocephalus during pregnancy.One hundered and twenty two aborted women were selected for this study. Serum samples were collected form Al-Kadhmia and Kamal Al-Samari Hospitals,and laboratories around Baghdad, and tested for specific IgG and IgM anti-toxoplasma antibodies to confirm toxoplasmosis in those women by using ELISA test.The result recorded that 51(41.8%) women had antibodies against Toxoplasma gondii, 25(59.5%) women were positive for IgG, and 17(40.5%) women were positive forIgM, while 9(17.6%)women were positive for both.